Паралельна робота трансформаторів в системі електропостачання шахти - Варецький, Ю. О.; Коновал, В. С.; Varetsky, Y.; Konoval, V. (Видавництво Львівської політехніки, 2020)
Увімкнення трансформаторів на паралельну роботу потребує врахування кількох важливих вимог. У процесі експлуатації систем електропостачання промислових підприємств іноді виникають ситуації, коли стає бажаним вмикати на паралельну роботу трансформатори, характеристики яких не зовсім відповідають такій процедурі. Якщо трансформатори ввімкнено на паралельну роботу, то будь-яка різниця між їхніми параметрами призводить до перерозподілу навантаження між ними порівняно з попереднім режимом, коли вони працювали ізольовано. Розглянуто проблему паралельної роботи трансформаторів різної потужності в системі електропостачання шахти, а також проаналізовано вплив конфігурації системи електропостачання та схем приєднання електроприймачів на розподіл навантажень між трансформаторами.

Connecting transformers in parallel requires a few of important requirements. During operation of the industrial supply power systems, there are sometimes situations when it becomes desirable to operate of parallel transformers, the characteristics of which do not quite correspond to such a procedure. When transformers are connected in parallel, any difference between their parameters causes the load to be redistributed between them compared to the previous operating mode they had been operating in isolation. The paper deals with the problem of different capacity transformers paralleling within the mine power supply system, and also analyzes the impact of the power supply system configuration and connection diagram of electric consumers on the load distribution between the transformers. According to the IEEE Standard C57.153™-2015, two or more transformers connected to common load buses should be considered as operating in parallel. All types of load, as well as capacitor banks, shunt reactors, or power sources can be connected to those buses. The primary windings of the transformers can be connected to common buses or buses that receive power from different lines. The IEEE Standard also describes general requirements to the paralleling transformers -general paralleling application (GPA) – when two or more regulated transformers are connected in parallel to the common source buses: · transformer ratios should be the same. · relative impedances of transformers should be the same and should have the same ratio of the reactance to the equivalent resistance of the windings. · transformers should have the same polarity of the secondary windings. · three-phase transformers should have the same phase sequence. · there should be no phase shift between the voltages of the secondary windings of the transformers. Obviously, under actual operating conditions, it is almost impossible to meet the described requirements due to possible differences in characteristics of the transformers and configurations of the electrical networks. The problem of parallel operation of transformers under the following conditions is of particular practical interest: · power supply of transformer primary windings from different power lines. · difference of relative impedances of parallel transformers under change of transformer ratios. In this case, the parallel operation of transformers should meet the requirements of voltage control on the load buses and minimize the circulating current due to inappropriate transformer ratios. Also, these conditions should be provided regardless of the power system configuration changes. A lot of studies are dedicated to the problem of paralleling power transformers and their control. But the authors did not find the studies concerning the impact of the power supply system configuration and the loads connection layout on loading the paralleled transformers. The paper discusses paralleling transformers in the existing mine power supply system, having a complex circuit configuration of connecting the loads to substation buses using current limiting reactors. Modeling of the power supply system operating conditions has been carried out on the platform of the DAKAR software. Through simulation results it can be concluded, that in the analysed mine power supply system within the operating voltage limits at the buses of the 6 kV switchgears and the operating load changes, it is feasible paralleling transformers T1 and T3. Under the parallel operation, transformer T1 will be unloaded and transformer T3 will be more loaded compared to their separate operation. The nature of the load sharing between the transformers depends on the voltage moduli on the contacts of the busbar switch before switching it on. The maximum load of the transformer T3 under the parallel operation does not exceed 87% of its rated capacity. The minimum values of circulating currents between transformers operating in parallel will in case of close value of voltage moduli at the contacts of the bus circuit breaker before switching it on. The load of the transformer T3 under the paralleling transformers depends on the load sharing between the switchgears P1 and P2 of the transformer T1. The greater the relative load of the switchgear P1, the lower the additional load on the transformer T3.
Parallel operation of transformers within the power supply system of a mine
Keywords: система електропостачання; паралельна робота трансформаторів; моделювання; режим роботи; активні та реактивні навантаження; напруга; power supply system; paralleling transformers; modeling; operating mode; active and reactive loads; voltage